EleQta ou ré-examiner les élections à partir des expériences africaines: le cas de l’élection présidentielle de 2016 au Congo-Brazzaville - Bazenguissa-Ganga, Rémy; Alighieri, Pietro di Serego (Africana Studia, 2020)
This article presents the method applied within the research project “Re-examining elections after African experiences”: this project allowed to gather and analyze through the EleQta digital platform more than 5,000 pieces of information about elections held in 12 countries throughout sub-Saharan Africa between 2015 and 2019. It will make use of the results of the enquiries conducted on the 2016 presidential elections in the Republic of Congo (Congo-Brazzaville) to describe the approach adopted and the fundamental assumptions of the project. Furthermore, it will defend the idea that the analysis of African electoral processes leads to redefine basic notions and to develop conceptual tools which can be applied to electoral processes in the West.